The Impact of Face Threatening Acts on Hearer (The Wife) Face in A Household Conflict: A Pragmatic Study - Sutiadi Rahmansyah; Tajudin Nur; Davidescu Cristiana Victoria Marta; Lia Maulia Indrayani (Hasanuddin University, 2020)
Conflict is a problem that is often faced in daily life, including husband and wife. Conflict in the household can lead to positive and negative things such as a divorce or violence in a household. The problem of conflict is closely related to the threat of “face” or a person self-esteem. The purpose of this article is to study the impact of face experienced by hearer (wife) in a household conflict that is particularly occurred on wife after her husband performs Face Threatening Acts. The method used in this research was qualitative, descriptive methods, i.e. it gives descriptive result about the impact of Face Threatening Acts usage and strategies in a household conflict obtained from several popular psychology books. The results showed that in general the impact of FTA used by a husband against his wife in the household conflict caused face loss on behalf of his wife (the loss of self-esteem). This happened because her feelings were more dominant and she generally avoided a conflict that could trigger further disputes with her husband to maintain her household.